2013
DOI: 10.1016/j.palaeo.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The lost paleosols: Masked evidence for emergence and soil formation on the Kimmeridgian Jura platform (NW Switzerland)

Abstract: Lagoonal carbonates of Kimmeridgian age in NW Switzerland formed in a tropical epeiric sea and exhibit indicators of subaerial emergence such as tidal biolaminites, desiccation cracks, flat pebble conglomerates, and fenestral structures. Additionally, 30 dinosaur tracksites from at least six stratigraphic intervals indicate repeated formation of land bridges between the platform and adjacent massifs. Populations of herbivorous and carnivorous dinosaurs necessitate substantial vegetation and consequently a soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 63 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…The widespread dinosaur track record of the Jura Mountains and the herein reported presence of giant theropods indicate that large parts of the Jura carbonate platform were emergent during several and prolonged time periods allowing the development of a soil (Waite et al 2013) and vegetation cover confirmed by an almost complete juvenile megalosaurid theropod specimen that was described by Rauhut et al (2012) from the Solnhofen Plattenkalke of Painten, SE Germany. This specimen is, as Jurabrontes, Late Kimmeridgian in age.…”
Section: Palaeo(bio)geographical Considerationsmentioning
confidence: 51%
“…The widespread dinosaur track record of the Jura Mountains and the herein reported presence of giant theropods indicate that large parts of the Jura carbonate platform were emergent during several and prolonged time periods allowing the development of a soil (Waite et al 2013) and vegetation cover confirmed by an almost complete juvenile megalosaurid theropod specimen that was described by Rauhut et al (2012) from the Solnhofen Plattenkalke of Painten, SE Germany. This specimen is, as Jurabrontes, Late Kimmeridgian in age.…”
Section: Palaeo(bio)geographical Considerationsmentioning
confidence: 51%
“…Marty ; Waite et al . ). A food source for the herbivorous dinosaurs was presumably present, and thus firm ground and freshwater must have been present in the vicinity.…”
Section: Geographical and Geological Settingsmentioning
confidence: 97%
“…In siliciclastic deposits, Thalassinoides is indicative of lower shoreface-offshore settings (Pemberton et al 2001;Uchman and Krenmayr 2004;Buatois and Mángano 2011;Chrząstek 2013;La Croix et al 2013). It is also reported from the inner-middle carbonate ramp (Knaust 1998;, and mostly from shallow carbonate deposits (Monaco and Giannetti 2002;Jach 2005;Waite et al 2008Waite et al , 2013Vlahovic et al 2011;Wiedl et al 2012Wiedl et al , 2013. Thalassinoides was described from the upper part of the shallowing upward cycle (Knaust 1998;Pérez-Valera and Pérez-López 2008;Pérez-López and Pérez-Valera 2012).…”
Section: Thalassinoides Ichnoassociation (Ia 3)mentioning
confidence: 99%